Review: Occurrence and Distribution of Galanin in the Physiological and Inflammatory States in the Mammalian Gastrointestinal Tract - Brzozowska, Marta; Całka, Jarosław (Frontiers in Immunology, 2021)
Galanin (GAL) is a broad-spectrum peptide that was first identified 37 years ago. GAL, which acts through three specific receptor subtypes, is one of the most important molecules on an ever-growing list of neurotransmitters. Recent studies indicate that the peptide is commonly present in the gastrointestinal (GI) tract and GAL distribution can be seen in the enteric nervous system (ENS). The function of the GAL in the gastrointestinal tract is, inter alia, to regulate motility and secretion. It should be noted that the distribution of neuropeptides is largely dependent on the research model, as well as the part of the gastrointestinal tract under study. During the development of digestive disorders, fluctuations in GAL levels were observed. Occurrence of GAL largely depends on the stage of the disease, for example in porcine experimental colitis caused by the infection with Brachyspira hyodysenteriae. Many authors have suggested that increased GAL presence is related to the involvement of GAL in organ renewal. Additionally, it is tempting to speculate that GAL may be used in the treatment of gastroenteritis. This review aims to present the function of GAL in the mammalian gastrointestinal tract under physiological conditions. In addition, GAL is undoubtedly involved in the regulation of inflammatory processes, and the aim of this publication is also to provide up-to-date knowledge of the distribution of GAL in experimental models of gastrointestinal inflammation, which in the future may help to accurately determine the role of the peptide in inflammatory diseases and its potential use in the treatment of gastrointestinal disorders.